Correction: Corrigendum: The solvation of electrons by an atmospheric-pressure plasma - Paul Rumbach (Nature Portfolio, 2016)
Nature Communications 6 Article number:7248 (2015); Published: 19 June 2015; Updated 6 June 2016. We have discovered an error in the original data analysis of our publication, which significantly impacts the model parameters derived from experiment. Specifically, the correction changes our estimations of the average penetration depth l and scavenging rate constants, but these new estimates do not change the overall physics conveyed in the Article.